AN OUTBREAK OF CONTAGIOUS ECTHYMA IN ADULT SHEEP - S. Barhoom, Salameh; M. Al-Darraji, Ali; S. Al-Bana, Anton; H.Al-Hadawi, Muthafar. (The Iraqi Journal of Veterinary Medicine, 1989)
This report documents an outbreak of contagious ecthyma in adult Iraqi sheep with high morbidity and low mortality. The clinioal findigs of the disease were: severe involvement of the buccal, gingival, labial and lingual mucosae. The causative agent was isolated in secondary lamb testis cells and identified by using a reference anti-contagious ecthyma antiserum.